STRATEGI KEUNGGULAN KOMPETITIF INDUSTRI KREATIF OLAHAN HASIL LAUT DENGAN PENDEKATAN METODE SOAR DAN QSPM - Narto, Narto; Ismail, Mohammad; Harimukti, Gatot Basuki (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
The seafood of the north coast of East Java has a variety of commodities, along with the growing creative industry is able to support the economy of coastal communities.  The obstacles faced by creative industry players are supply chains that are not well integrated, lack of sustainable product development and innovation. The research aims to explore the internal and external factors owned by creative industry players on the north coast of East Java, coastal industry players have a major role in supporting the economic sustainability of coastal communities and developing alternative strategies for processed seafood creative industries that have a competitive advantage. Mapping of internal factors is obtained through the IFAS matrix with a score of 3.1909 while the EFAS matrix score value is 2.8712. The preparation of alternative strategies using SOAR analysis obtained 5 alternative strategies and through the QSPM matrix obtained the greatest strategic weight, namely optimising the management of biological resources to improve the national economy through the number of exports of marine and fishery products.  To realise this strategy, sustainable steps are needed by improving the supply chain starting from providing subsidised fuel oil for fishermen to reduce operational costs, downstreaming the seafood processing industry, product innovation tailored to each export destination country.